Key determinants of intention to visit halal tourism in Madura - Nurita Andriani; Miftahul Jannah; Very Andrianingsih (al-Uqud : Journal of Islamic Economics, 2022)
The launch of halal tourism is based on the consideration that Indonesia is the largest Muslim majority country in the world, namely 207 million people. This study aims to analyse the potential of halal tourism in Madura with digital technology, access, value-added, and facilities mediated by e-marketing to see the intention to visit halal tourism. The research method used is Structural Equation Modeling with Smart Partial Least Square (PLS). The sample of this study was collected through a questionnaire from 187 tourists who were travelling in Madura halal tourism destination as respondents. The study results indicate that either directly or mediated by e-marketing, access significantly affects the intention to visit halal tourism. On the other hand, technology innovation and value-added have no significant effect. Meanwhile, facilities and e-marketing also directly affect the intention to visit halal tourism. Overall, to increase the potential for halal tourism visits in Madura, it needs easy access, good e-marketing and supporting facilities because the Madura area has many halal tourist destinations. The added value presented as an opportunity to see original regional merchandise, regional performances, and innovative technology has not become a priority for tourists to have halal tourism intention in Madura Island. This study provides research and practical implications for stakeholders related to halal tourism in Madura.